2020
DOI: 10.3390/coatings10030249
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Wear Behavior of PEO Coatings on D16T Aluminum Alloy with Different Concentrations of Graphene

Abstract: The effect of added graphene concentration on the microstructure, phase composition, corrosion-and wear-resistance of plasma electrolyte oxidation (PEO) coatings formed on D16T aluminum alloy in silicate electrolyte with different concentrations of graphene were investigated. The results show that the morphologies of the coatings with graphene were obviously different ascribed to the mode of graphene incorporated into the coating. The coatings consisted of mainly α-Al 2 O 3 , γ-Al 2 O 3 , and Al, which were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Such a porous structure is common for MAO coatings, which is due to micro-discharges occurring during the MAO process [27]. Although the pores can negatively affect the anti-corrosion and wear-resistant properties of the coatings, such a porous structure has a positive effect on the attachment of cells to the surface for biomedical applications [55][56][57]. In the present case, the arithmetic average of the roughness profile (R a ) and the maximum roughness (R z ) of MAO 1 and MAO 3 coatings have approximately the same values (Figure 3B and SI Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Such a porous structure is common for MAO coatings, which is due to micro-discharges occurring during the MAO process [27]. Although the pores can negatively affect the anti-corrosion and wear-resistant properties of the coatings, such a porous structure has a positive effect on the attachment of cells to the surface for biomedical applications [55][56][57]. In the present case, the arithmetic average of the roughness profile (R a ) and the maximum roughness (R z ) of MAO 1 and MAO 3 coatings have approximately the same values (Figure 3B and SI Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…D16T aluminum alloy samples were treated by a pulsed DC power supply (t on :t off = .4 ms:3.6 ms) under a constant voltage regime (500 V) for 10 min. Based on the previous research, 28,29 the base electrolyte and the addition concentration of graphene have been optimized. Meanwhile, the good performance of the aluminum alloy PEO coating can be obtained when 2-g/L graphene was added into the electrolyte.…”
Section: Materials and Experimental Processmentioning
confidence: 99%
“…Regarding the Aluminum PEO, reports in the literature have described the incorporation of particles into the oxide coating from the electrolyte to enhance their corrosion resistance, wear, and tribological properties [12][13][14][15], catalytic activity [16][17][18], magnetic properties [19,20], and antimicrobial properties [21][22][23][24][25][26]. Studies that focus on improving the corrosion resistance and tribological properties reported the use of carbon-based additives [12,13] and α-Al 2 O 3 [14], and ZrO 2 [15] powders in the electrolyte. In addition, W, Co, and Ni species are reported as an additive in PEO electrolytes to improve the catalytic properties of alumina coatings in thiophene oxidation [16] and CO conversion to CO 2 [17,18].…”
Section: Introductionmentioning
confidence: 99%